Solusi Numerik Model Matematika SIPAS dalam Penyebaran Praktik Monkey Business dengan Metode Adams-Bashforth-Moulton - Muhammad Abdy; Irwan, Irwan; Anjani, Variska (Journal of Mathematics: Theory and Applications, 2024)
This research is applied research to determine the numerical solution for the SIPAS mathematical model for the spread of monkey business practices using the Adams-Bashforth-Moulton method. The epidemic model for the spread of monkey business practices is susceptible, infected, practiced, and awareness (SIPAS). The discussion begins by determining the initial solution using the fifth order Runge-Kutta method, prediction and correction values using the Adams-Bashforth-Moulton method, simulation and analysis of the results. In this research, it was found that the Adams-Bashforth- Moulton method predicts an increase in the population who know a viral business and become vulnerable(S) due to the number of residents who know a viral business and the population who are aware of the dangers of monkey business practices. Meanwhile, the population that is interested (I), practiced (P) and awareness (A), on the other hand, has decreased and disappeared completely due to a population that has stopped following a viral business and is aware of the dangers of monkey business practices. After carrying out simulations and analyzing the results, it can be seen that the Adams-Bashforth-Moulton method can be used to determine the numerical solution for the SIPAS mathematical model for the spread of monkey business practices.